Effects of omega-3-enriched eggs on HDL cholesterol: an in vivo study - Sahabuddin, Ratu Balqis Naailah; Kamaluddin, Irna Diyana Kartika; Khalid, Nur Fadhillah; Gayatri, Sri Wahyuni; Masdipa, Andi (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Low high-density lipoprotein (HDL) cholesterol remains an important risk factor for cardiovascular disease. Functional foods enriched with omega-3 fatty acids may offer a practical dietary approach to improving lipid profiles. Purpose: To evaluate the effects of omega-3 enriched eggs on HDL cholesterol levels in Wistar rats compared with regular eggs and a standard diet. Methods: Fifteen male Wistar rats were randomly assigned to three groups: control (standard diet), regular egg, and omega-3 enriched egg. Egg yolk preparations were administered orally via gastric gavage for 14 days. HDL cholesterol was measured before and after the intervention using an enzymatic colorimetric assay. Data were analyzed using paired t-tests for intragroup comparisons and one-way ANOVA with Tukey post-hoc testing for between-group differences. Results: The omega-3 enriched egg group showed a significant increase in HDL cholesterol (from 39.83 ± 6.08 to 66.32 ± 4.35 mg/dL; p = 0.001), while increases in the regular egg (p = 0.093) and control groups (p = 0.454) were not significant. ANOVA indicated significant differences among groups (F (2,12) = 6.308, p = 0.013), with post-hoc analysis confirming higher HDL levels in the omega-3 group compared with the control group (p = 0.011). Conclusion: Omega-3 enriched eggs elicited a substantial increase in HDL cholesterol compared with regular eggs and a standard diet, supporting their potential as a functional food for improving lipid profiles. Further studies with larger samples, extended intervention periods, and human participants are recommended to validate their clinical relevance.